2018
DOI: 10.1016/j.solmat.2017.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Refractive indexes and extinction coefficients of n- and p-type doped GaInP, AlInP and AlGaInP for multijunction solar cells

Abstract: The optical properties of p-type, n-type and nominally undoped (Al x Ga! -Jyln! _ y P layers have been determined in a wide spectral range. The layers under study have been chosen with compositions and dopant concentrations which make them interesting for their use in III-V multijunction solar cells. The layers have been measured by variable angle spectroscopic ellipsometry and, irrespective of composition and doping, their optical response has been modelled using the same model dielectric function consisting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 43 publications
0
31
0
Order By: Relevance
“…Theoretical modelling. To model the EQE, we rst calculated the photon ux at different depths inside the structure by applying the generalized matrix method as described by E. Centurioni, 61 with refractive indexes taken from Aspnes et al 62 and Ochoa-Martínez et al 63 In this context, the photon ux at a given point x is the total fraction of photons from an arbitrary initial ux impinging the front of the structure that propagate through point x, including photons that have been re ected at the interfaces and taking into account their interference. The wavelength-dependent light ux at the interfaces between layers is particularly important because it will be used in the EQE model.…”
Section: Methodsmentioning
confidence: 99%
“…Theoretical modelling. To model the EQE, we rst calculated the photon ux at different depths inside the structure by applying the generalized matrix method as described by E. Centurioni, 61 with refractive indexes taken from Aspnes et al 62 and Ochoa-Martínez et al 63 In this context, the photon ux at a given point x is the total fraction of photons from an arbitrary initial ux impinging the front of the structure that propagate through point x, including photons that have been re ected at the interfaces and taking into account their interference. The wavelength-dependent light ux at the interfaces between layers is particularly important because it will be used in the EQE model.…”
Section: Methodsmentioning
confidence: 99%
“…Since photogenerated carriers must reach the junction before being collected, the average distance to cover is significantly shorter in this configuration than in RHJs. In order to provide further insight on the dependence between the junction position and the collection efficiency, Fig.6 presents the modelled IQE of both configurations -FJ and RHJusing the Hovel method [27] and the optical data used corresponding to our measured disordered-GaInP material [28]. To strictly focus on the junction position, the total thickness of GaInP is always 850 nm and the minority carrier properties -diffusion length (Lm) and lifetime (τm)-are kept constant for both n and p-type GaInP.…”
Section: Solar Cells Characterizationmentioning
confidence: 99%
“…The optical properties of Semiconductor Nanowires (NWs) (high refractive index, light confinement, and uniform diameter) offer excellent base Nanoscale optical circuits (Chad Husko. et al, 2018;Xiaojie, 2015;Peidong, 2010;Xing, 2014;Habeom et al, 2017;Muskens et al, 2008;Muskens et al, 2009;Ochoa-Martínez et al, 2018). In (Chad Husko.…”
Section: Introductionmentioning
confidence: 99%
“…Xiaojie, et al (2015), explained the use of nanocircuits in the study of neural circuits, and Muskens et al, (2008), shows fascinating progress in the field of III-V Nanowires solar cells because of the low cost and advanced techniques of fabrication. Ochoa-Martínez, et al, (2018), and his colleges concluded, the determination of the optical constants of III-V phosphide-based materials with the typical doping levels and growth conditions applied in the fabrication of multi-junction solar cells is essential to improve the accuracy of the models used to predict the solar cell performance. A40% efficiency reached in solar cells by using multi-layer semiconductors (Yamaguchi et al, 2003;Kang et al, 2004).…”
Section: Introductionmentioning
confidence: 99%